Analysis of TIX ID Application User Satisfaction in Depok City Using the End User Computing Satisfaction (EUCS) Method - Wirdiyanto, Afri Wahyu (Information Technology and Systems, 2024)
TIX ID is an official application from PT Nusantara Elang Sejahtera, and was released to meet the needs of users among the people of Depok. The purpose of this study is to find out whether there is an influence of content, accurancy, format, ease of use and timeliness on the satisfaction of TIX ID application users and to find out whether there is an influence on the level of satisfaction of TIX ID application users as a medium for booking cinema tickets. The method used in this study is End User Computing Satisfaction (EUCS) which consists of five factors, namely: content, accuracy, form, ease of use, and timeliness. The data collection process was carried out by distributing questionnaires to people who use the TIX ID application in Depok. The sampling technique uses random sampling. The data processing method carried out in this study uses validity tests, reliability tests, and hypothesis tests processed using SPSS software. The results of hypothesis testing there are 4 variables that have an effect, namely accuracy, format, ease of, timeliness and there is 1 variable that has no effect, namely content. Based on the correlation analysis, R2 of 0.657 showed that the satisfaction variable could be explained by the variables content, accuracy, format, ease of use and timeliness of 65.7%